DNA-PK promotes activation of the survival kinase AKT in response to DNA damage through an mTORC2-ECT2 pathway - Liu, Liu; Dai, Xiaoming; Yin, Shasha; Liu, Pengda; Hill, Elizabeth G; Wei, Wenyi; Gan, Wenjian (Science signaling, 2022)
The kinase AKT (also known as protein kinase B) is a key regulator of cell proliferation, survival, and metabolism. In addition to being activated by growth factors, AKT is activated in response to DNA damage. Here, we found that the DNA damage response kinase DNA-PK sustains cell survival through a phosphorylation event that leads to increased AKT activity. In various cancer and noncancer cells in culture, DNA damage caused by ionizing radiation or topoisomerase inhibitors triggered DNA-PK–dependent phosphorylation of the mTOR complex 2 (mTORC2) subunit Sin1, which enabled its interaction with the guanine nucleotide exchange factor ECT2. Depleting Sin1 or ECT2 or disrupting the protein interaction or catalytic function of ECT2 attenuated DNA damage–induced AKT activation, thereby enhancing cellular sensitivity to DNA-damaging agents. Our findings elucidate a mechanism mediating DNA damage–induced AKT activation and cell survival.